Europe and Central Asia Economic Update, Spring 2019 : Financial Inclusion - World Bank (Washington, DC: World Bank, 2019)
Financial services can help drive development by facilitating people’s investments in their health, education, and businesses, and making it easier for people to manage emergencies. There is great variation in financial inclusion in the Europe and Central Asia region. Some countries have seen significant growth in account ownership, despite starting from a low base. These experiences underline the potential role of digital payments in driving financial inclusion. But nearly 30 percent of unbanked adults report trust in banks as a barrier, which is nearly double the developing country average. And in some countries, gender gaps in account ownership remain significant. Given the heterogeneity of experiences, there are ample opportunities for countries in the region to learn from each other and contribute to the rich research and operational agenda going forward.